KHILAFAH DALAM WAWASAN AL-QURâAN: Pendekatan Semantik-Historis - Nadhiroh, Wardatun (Jurnal Ilmu Ushuluddin, 2014)
Concept of Khilafah apparently reaps controversy among community. It is always identified as one of governmentalsystems. This work uses semantic and historical approach to restudy the meaning of Khilafah from many aspects, suchas study of literal meaning, of Qurâanic contexts, and of developed-meaning from beginning until now. Actually,Khilafah is a concept about giving sovereignty by the highest authorization to capable person in permitting to manageand perform the businesses that are handed over to him. Khilafah meant as one of governmental system after AbuBakar, the first leader of Muslims after Rasulullah died, labeled him as Khalifati Rasulillah, and then the governmentalsystem of Khilafah started. However, Khilafah is only being an alternative choice of governmental system nowthat must not be implemented.